Investment Repercussions - Lachmann, L. M. (Quarterly Journal of Economics, 1948)
I. Introduction, 698. — II. The relation of new investment to changes in the use of existing capital, 700. — III. The analysis applied to three concrete problems: (a) vertical integration, 706. — IV. (b) Development of backward areas, 708. — V. (c) The trade cycle, 711.